(untitled) (Research Journal of Mathematics & Technology, 2022)
Artificial Intelligence (AI) is one of the most crucial factor affecting future career choice of students. Accordingly, we offered students a semester-long Introductory Mathematics for Artificial Intelligence course. The course was developed to provide undergraduate students with various majors to navigate their career opportunities in AI-related jobs. This paper presents the newly published textbook and an online mathematics laboratory that integrated effective technology for this introductory course. In addition, we introduce a process-driven evaluation method based on the Problem/Project-Based Learning (PBL) report that worked well for this course. We also share trails of communications with our students and added the results of our students' performance analysis using principal component analyses (PCA) with the data generated from the class.